ANALYSIS OF THE IMPLEMENTATION OF ACCOUNTING POLICIES AND RECORDING OF FIXED ASSETS QUALITY OF FINANCIAL REPORTS IN THE EAST LUWU REGIONAL GOVERNMENT - Rachmawaty; Salju; Rahmawati; Goso (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research aims to determine and explain the analysis of accounting policies and asset recording on the quality of financial reports in the East Luwu Regency Regional Government. This research method uses a qualitative method with a descriptive approach. Data is processed through observation , interviews, documentation and raising case examples. The population and sample used are conditions in the OPD within the East Luwu Regency Regional Government. The sources taken in this research were employees at the Regional Finance and Assets Agency who handle the Implementation of Accounting Policies and Regional Asset Management. Based on the results of the research carried out, basically the preparation of Regional Government Financial Reports has implemented Government Accounting Standards Number 71 of 2010 and uses a Technology Information System using SIPD RI in accordance with the mandate of Minister of Home Affairs Regulation Number 70 of 2019. The results of this research found that there is OPD in the implementation of expenditure as stated in planned, expenditure on goods and services for maintenance of office buildings does not meet the requirements to be recognized as expenditure on goods and services and there is expenditure on additional power for maintenance of office buildings. The Accounting and Asset Recording Policy recognizes that expenditure on building maintenance is categorized as capital expenditure because it meets 3 main requirements namely: The principle of benefits exceeding 12 months, meeting the capitation value of assets and increasing the value of assets, so that when recording Fixed Assets, maintenance of Office Buildings is recorded in Office Building assets and additional electrical power is recorded in Fixed Assets, Roads, Irrigation and Networks considering that additional electrical power comes in at network category.